OPTIMALISASI PEMBERIAN PENYULUHAN KESEHATAN DAN DEMONSTRASI CUCI TANGAN PAKAI SABUN (CTPS) YANG BAIK DAN BENAR DI SD NEGERI MOJOREJO 2 KABUPATEN SRAGEN - Noorratri, Erika Dewi; Sari, Irma Mustika; Hartutik, Sri (Community Development in Health Journal, 2023)
Introduction & Aim: Many people or students, especially elementary school students, already know to wash their hands with just water.but they don’t know how to use soap. More than 10 millon childres in Indonesia aged less than 5 years are estimated to die each year, around 20% die due to diarrhea infections. Target and outcome: One hundres percent of participants are able to understand the importance of preventing diseases caused by germs and bacteria that stick to their hands, participants are able to wash thei hands with good and correct soap independently and Community Service journal Method of Activity: used is giving material to be delivered using visual media, lectures using power point and discussion or question, and demonstratios. Results: There is an increase in knowledge before and after being given helath education and demonstrations of washing hands with soap (CTPS). Discussion: Hand washing using soap is very important as a way to prevent diarrhea. The behavior of washing hands with soap has generally been taught and introduced to childres from an early age, not only in the home, community but also in the school.